2011
DOI: 10.1007/s10555-011-9301-4
|View full text |Cite
|
Sign up to set email alerts
|

COX inhibitors directly alter gene expression: role in cancer prevention?

Abstract: Inflammation is an important contributor to the development and progression of human cancers. Inflammatory lipid metabolites, prostaglandins, formed from arachidonic acid by prostaglandin H synthases commonly called cyclooxygenases (COXs) bind to specific receptors that activate signaling pathways driving the development and progression of tumors. Inhibitors of prostaglandin formation, COX inhibitors, or nonsteroidal anti-inflammatory drugs (NSAIDs) are well documented as agents that inhibit tumor growth and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 115 publications
0
37
0
Order By: Relevance
“…Inhibition of COX is generally thought to be the primary mechanism responsible for their antineoplastic activity, although numerous studies have concluded that alternative targets may be involved, as reviewed previously (24). Given that the use of NSAIDs for cancer chemoprevention is limited by COX-dependent toxicities, identifying the relevant targets that mediate their antitumor properties provides an opportunity to develop safer and more efficacious derivatives, or new chemical entities.…”
Section: Introductionmentioning
confidence: 96%
“…Inhibition of COX is generally thought to be the primary mechanism responsible for their antineoplastic activity, although numerous studies have concluded that alternative targets may be involved, as reviewed previously (24). Given that the use of NSAIDs for cancer chemoprevention is limited by COX-dependent toxicities, identifying the relevant targets that mediate their antitumor properties provides an opportunity to develop safer and more efficacious derivatives, or new chemical entities.…”
Section: Introductionmentioning
confidence: 96%
“…NAG-1 is also known as macrophage inhibitory cytokine-1, placental transforming growth factor-β, prostate-derived factor, placental bone morphogenetic protein, or growth differentiation factor-15 (GDF-15) [6,7]. NAG-1 is synthesized as a 308-amino acid pro-peptide and secreted as a mature protein after proteolytic cleavage [6,7,8,9,10]. The secreted form is present in the blood of humans and media of cultured cells expressing NAG-1 [9].…”
Section: Introductionmentioning
confidence: 99%
“…NAG-1 is synthesized as a 308-amino acid pro-peptide and secreted as a mature protein after proteolytic cleavage [6,7,8,9,10]. The secreted form is present in the blood of humans and media of cultured cells expressing NAG-1 [9]. Both the pro-form and secreted form are likely to play central roles in the biological activity of NAG-1 [6,7,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These side effects have been attributed to the inhibition of COX activity, with several studies implicating a COX-dependent mechanism. [8][9][10] Mitochondria have been the subject of recent research as a principal target of NSAID-induced toxicity. [11][12][13][14][15][16] Fenamic acid is an aromatic amino acid that is also called N-phenylanthranilic acid (NPA).…”
mentioning
confidence: 99%